Physical Properties of Biodegradable Chitosan-Cassava Starch Based Bioplastic Film Mechanics - Kusumawati, Rinta; Syamdidi; Abdullah, Akbar Hanif Dawam; Nissa, Rossy Choerun; Firdiana, Bonita; Handayani, Rini; Munifah, Ifah; Dewi, Fera Roswita; Basmal, Jamal; Wibowo, Singgih (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Petroleum-derived plastics are widely used but pollute the environment significantly. The development of biodegradable plastics is urgently needed to be replaced. The mechanism for making bioplastic films from cassava starch-chitosan/glycerol uses a double-screw extruder process. The film took into account the multi-hydroxyl capacity of starch by combining glycerol (in a ratio of 3:1 w/w) and chitosan (at concentrations of 0.5, 1.0, and 1.5% (w/w). The impact of chitosan involvement on the characteristics of the bioplastic material was studied, including physical, thermal, mechanical, and biodegradability properties. The findings showed that using chitosan as a filler in cassava starch bioplastics resulted in bioplastic films with high compressive capacity and water resistance. The resulting biopolymer’s contact angle was increased by including C-O functional groups in the molecule, as evidenced at a wavelength of 1028 cm-1 of the FTIR spectra. The contact angle was increased from theta = 65.3059 ± 2.7936◦ to theta = 68.6047 ± 3.2391◦. An increase in tensile strength was also observed, indicating increased stiffness compared to chitosan-free bioplastics. The best bioplastic blend was the formulation of cassava starch and glycerol containing 0.5% chitosan. Bioplastic has physical properties of density 0.8625 ± 0.0277 g/mL; contact angle 68.6046 ± 3.2391◦; water uptake 11.0660 ± 0.3709%; tensile strength 2.0181 ± 0.0594 MPa; elongation 54.2243 ± 3.2623%; thermal 137.5◦C; moisture content 4.9464 ± 0.1172%; and the fastest biodegradation rate. The bioplastic synthesized in this study is readily biodegradable in the natural environment, making it highly sustainable and more environmentally friendly, and it can be a viable substitute to reduce the use of petroleum-based bioplastic.